(untitled) (Journal of the College of Basic Education, 2025)
This article seeks to discuss the content related to the Iraqi Revolution of 1920 and its revolutionary and political environment within a group of Turkish newspapers between the years (1920-1921) with both those newspapers affiliated with the Istanbul government representing the Ottoman state on the one hand, and those affiliated with the Kemalist Revolution on the other. This discussion will attempt to reveal the content of these newspapers and will point out the sensitive nature of the Ottoman government’s dealings with any revolutionary movement in the region, as well as its efforts to improve its relations with the Allies and to restore its ties with the Arab and Islamic region. It will also point out the tone of the Kemalist newspapers, which was completely different from the Istanbul newspapers, and which would provide clear media support for the Revolution of 1920. It should be emphasized that discussing any logistical or military support should be discussed elsewhere in this article.